Analysis of Manual Material Handling Operators at UKM XYZ - Vidi Agung Fragastia; Rasyid Sunara Zaini (Industrial Engineering System and Management Journal, 2022)
This study aims to analyze the posture value of manual material handling workers on operators at UKM XYZ. UKM XYZ is engaged in processed snacks made from cassava. One of the activities carried out by humans, especially in material handling (manual material handling) is carried out at workstations. These activities still use traditional machines and simple equipment so that the operator performs long bending activities. This can cause complaints of musculoskeletal disorders (MSDs). The work carried out by the operator is on the workers in the third work element (frying) and checking the heater. After conducting an interview with the operator at the work station, the operator felt a complaint of pain in the shoulder. If left unchecked, it will cause skeletal muscle injury. The purpose of this study was to determine and measure the operator's workload based on the calculation of RWL (Recommended Weight Limit). From the measurement results of the operators at the work station, it was found that this activity is a light activity based on the calculation of energy consumption and the actual lifting load is below the recommended load with a Lifting Index (LI) level <= 1, meaning that the weight of the lifted load does not exceed lifting limits and does not carry the risk of spinal cord injury.